Two Novel Small Molecule Donors and the Applications in Bulk-Heterojunction Solar Cells - Qi, Xin; Lo, Yuan-Chih; Zhao, Yifan; Xuan, Liyang; Ting, Hao-Chun; Wong, Ken-Tsung; Rahaman, Mostafizur; Chen, Zhijian; Xiao, Lixin; Qu, Bo (Frontiers in Chemistry, 2018)
Two novel small molecules DTRDTQX and DTIDTQX, based on ditolylaminothienyl group as donor moiety and quinoxaline as middle acceptor moiety with different terminal acceptor groups were synthesized and characterized in this work. In order to study the photovoltaic properties of DTRDTQX and DTIDTQX, bulk-heterojunction solar cells with the configuration of FTO/c-TiO2/DTRDTQX(or DTIDTQX):C70/MoO3/Ag were fabricated, in which DTRDTQX and DTIDTQX acted as the donors and neat C70 as the acceptor. When the weight ratio of DTRDTQX:C70 reached 1:2 and the active layer was annealed at 100°C, the optimal device was realized with the power conversion efficiency (PCE) of 1.44%. As to DTIDTQX:C70-based devices, the highest PCE of 1.70% was achieved with the optimal blend ratio (DTIDTQX:C70 = 1:2) and 100°C thermal annealing treatment. All the experimental data indicated that DTRDTQX and DTIDTQX could be employed as potential donor candidates for organic solar cell applications.